Trends in TaRL-Based Student Worksheet Development for Indonesian Language Learning in Elementary Schools: A Systematic Literature Review (2020–2025) - Anisa Ayu Pramesti; Nuni Widiarti; Bambang Subali (FKIP - Universitas Riau, 2026)
This study examines trends in the development of Teaching at the Right Level (TaRL)–based student worksheets and their relationship with collaboration skills in Indonesian language learning at the elementary school level during the 2020–2025 period. The main issue is the limited integration of collaboration skills in student worksheets, particularly in lower grades, causing learning to emphasize cognitive aspects. This study employed a Systematic Literature Review (SLR) and bibliometric analysis using VOSviewer software. Data were collected through the Publish or Perish application connected to Google Scholar and Scopus. An initial search identified 300 articles, which were filtered based on inclusion criteria to obtain 100 eligible studies. From these, 25 representative articles were selected for qualitative analysis. The results show that: (1) TaRL effectively improves basic literacy-numeracy skills; (2) student worksheets development focuses mainly on cognitive domains, with limited attention to social and affective aspects; (3) collaboration skills among lower-grade elementary learners remain underexplored; and (4) comprehensive integration of TaRL, student worksheets, and collaboration skills in Grade I Indonesian language learning has not yet been comprehensively addressed. These findings indicate a research gap and opportunities for developing collaboration-oriented TaRL-based student worksheets to support 21st-century skills.